(untitled) (Research, Society and Development, 2021)
The guabijú (Myrcianthes pungens) is a fruit native from Brazil, characterized by its pleasant sweet flavor, yellow pulp and purple skin in the ripe stage. Its maturation period occurs between december and april in the southern regions of Brazil. The aim of this study was to evaluate the physico-chemical characteristics of guabijú in natura and lyophilized from two different harvest times (December and January). The proximal composition, bioactive profile (anthocyanins, phenolic compounds, and antioxidant activity), mineral profile (Ca, Cu, Fe, Mg, Mn, K, and Zn), and color parameters (L*, a*, and b*) were evaluated. The fruits from January presented a higher content of carbohydrates, reducing sugars, antioxidant potential, and more intense characteristic color, while the fruits from December showed a higher total anthocyanin and mineral content. Moreover, the samples submitted to lyophilization showed good retention of bioactives, highlighting as a suitable method of processing to increase the stability without profound physico-chemical changes. In the colorimetric analysis, the lyophilized samples have a higher intensity of red color, especially in guabijú from January. Both guabijú forms (in natura and lyophilized) from two harvesting times were considered a source of bioactives, with great potential for application in foods.